LSMS+ Program in Sub-Saharan Africa : Findings from Individual-Level Data Collection on Labor and Asset Ownership - Hasanbasri, Ardina (World Bank, Washington, DC, 2021)
Established in 2016, the World Bank living standards measurement study - plus (LSMS+) program works to enhance the availability and quality of intra-household, self-reported, individual-disaggregated survey data collected in low- and middle-income countries on key dimensions of men’s and women’s economic opportunities and welfare. This report presents findings on gender differences in labor market outcomes and ownership of physical and financial assets in Sub-Saharan Africa, based on the national surveys that have been implemented by the respective national statistical offices (NSOs) in Ethiopia, Malawi, and Tanzania over the period 2016-2020, with support from the LSMS+ program.